(untitled) (Bangladesh Journal of Dental Research & Education, 2013)
This was a qualitative study conducted in one government and one private dental college selected purposively. Study population was final year clinical teachers of selected Dental Colleges. A total of 35 teachers (twenty from private dental college and fifteen from govt. dental college) participated in this study. An open ended questionnaire was developed for in-depth interview of the teachers. Analysis of the teachers’ responses revealed that their views were related to only three issues: (1) Organization of teaching experiences: Make objectives realistic and practical, feedback, (2) Clinical experiences related factors: Students active involvement, working with patient and their family/ attendant and (3) Supervisory factors: Knowledgeable faculty, positive attitude of teachers. Dental faculty involved in teaching activities should be encouraged to take formal training. Study recommended increasing time and patient availability in clinical setting for effective clinical learning and skill competency. DOI: http://dx.doi.org/10.3329/bjdre.v3i1.16592 Bangladesh Journal of Dental Research & Education Vol.3(1) 2013: 25-29